Effect of Product Quality and Trust on Customer Loyalty of Tabita Skincare Cream - Niar Astaginy; Fitri Kumalasari; Irasmia Irasmia (Jurnal Ilmiah Manajemen dan Bisnis, 2023)
This research is motivated by the existence of gaps in research results and is reinforced by the phenomenon that occurs in Tabita Skincare Cream users in Kolaka Regency, which are still widely used by consumers, but these cosmetic products have not been registered with the BPOM agency. This study aims to measure the effect of product quality and trust on customer loyalty to Tabita skincare cream users in the Kolaka Regency. This study uses a quantitative approach with a purposive sampling technique. The sample used was 50 respondents. Data analysis was processed using structural equation modeling (SEM) with PLS analysis techniques. The study results indicate that product quality has a positive and significant effect on customer loyalty to Tabita skincare cream users in Kolaka Regency. This is evidenced by the t-count, which is 9,816, which is higher than the t-table value of 1,299, and the trust variable also has a positive and significant effect on customer loyalty because the t-count value obtained from the results of data processing is 2.505 higher than the value t-table is 1.299. Then the product quality and trust variables have a positive and significant effect on customer loyalty in the influence of 51.1%, and other variables explain the remaining 48.1% besides those studied in this study.